Picophytoplankton dynamics in a large temperate estuary and impacts of extreme storm events - Ryan W. Paerl (Nature Portfolio, 2020)
Abstract Picophytoplankton (PicoP) are increasingly recognized as significant contributors to primary productivity and phytoplankton biomass in coastal and estuarine systems. Remarkably though, PicoP composition is unknown or not well-resolved in several large estuaries including the semi-lagoonal Neuse River Estuary (NRE), a tributary of the second largest estuary-system in the lower USA, the Pamlico-Albemarle Sound. The NRE is impacted by extreme weather events, including recent increases in precipitation and flooding associated with tropical cyclones. Here we examined the impacts of moderate to extreme (Hurricane Florence, September 2018) precipitation events on NRE PicoP abundances and composition using flow cytometry, over a 1.5 year period. Phycocyanin-rich Synechococcus-like cells were the most dominant PicoP, reaching ~ 106 cells mL−1, which highlights their importance as key primary producers in this relatively long residence-time estuary. Ephemeral “blooms” of picoeukaryotic phytoplankton (PEUK) during spring and after spikes in river flow were also detected, making PEUK periodically major contributors to PicoP biomass (up to ~ 80%). About half of the variation in PicoP abundance was explained by measured environmental variables. Temperature explained the most variation (24.5%). Change in total dissolved nitrogen concentration, an indication of increased river discharge, explained the second-most variation in PicoP abundance (15.9%). The short-term impacts of extreme river discharge from Hurricane Florence were particularly evident as PicoP biomass was reduced by ~ 100-fold for more than 2 weeks. We conclude that precipitation is a highly influential factor on estuarine PicoP biomass and composition, and show how ‘wetter’ future climate conditions will have ecosystem impacts down to the smallest of phytoplankton.